Who trusts? Ethnicity, integration, and attitudes toward elected officials in urban Nigeria - Adrienne LeBas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In the developing world, clientelism is common. In Africa, public office is often used to redistribute resources to ethnically defined constituencies, and this form of clientelistic exchange is a key determinant of vote choice. Does clientelistic exchange shape trust in elected officials as well? And does it continue to do so as cross-ethnic contact and integration increase? This paper uses public opinion data from urban Nigeria to investigate how an individual's social position and experiences with the state affect trust in elected officials, especially at the local level. The paper finds that the trust deficit associated with local ethnic minority status does not significantly diminish as these individuals integrate. For members of locally dominant groups, greater cross-ethnic contact and lessened reliance on ethnicity actually dampen expressed trust in local elected officials. These findings suggest the need for greater attention to cross-ethnic contact when evaluating the political implications of ethnic inequality.
Keywords: H11; H41; H70; N47; N97; 330; trust; identity; politics; ethnicity; clientelism; urban politics; Nigeria